2008
DOI: 10.1063/1.2901170
|View full text |Cite
|
Sign up to set email alerts
|

Critical dynamics of ballistic and Brownian particles in a heterogeneous environment

Abstract: The dynamic properties of a classical tracer particle in a random, disordered medium are investigated close to the localization transition. For Lorentz models obeying Newtonian and diffusive motion at the microscale, we have performed large-scale computer simulations, demonstrating that universality holds at long times in the immediate vicinity of the transition. The scaling function describing the crossover from anomalous transport to diffusive motion is found to vary extremely slowly and spans at least five … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
112
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 75 publications
(127 citation statements)
references
References 63 publications
14
112
0
1
Order By: Relevance
“…Recently, it was shown that the diffusion coefficient for an all-cluster average vanishes as D(n) ∼ (n * c − n * ) µ with a value µ = 2.88 [30,31]. Since only particles that are located in the percolating clusters can contribute to diffusion, we anticipate D(n) ∼ D ∞ (n)P ∞ (n) and infer the scaling relation µ ∞ = µ − β = 2.47.…”
Section: Diffusion Coefficientsmentioning
confidence: 59%
See 2 more Smart Citations
“…Recently, it was shown that the diffusion coefficient for an all-cluster average vanishes as D(n) ∼ (n * c − n * ) µ with a value µ = 2.88 [30,31]. Since only particles that are located in the percolating clusters can contribute to diffusion, we anticipate D(n) ∼ D ∞ (n)P ∞ (n) and infer the scaling relation µ ∞ = µ − β = 2.47.…”
Section: Diffusion Coefficientsmentioning
confidence: 59%
“…4. Choosing C ∞ = −0.53 t y 0 the data nicely collapse on a single master curve although the improvement is less satisfactory than for the all-cluster average [30,31] or in two-dimensional transport on a lattice [34]. The reason may be traced back to the slower convergence of the diffusion coefficients identified in the inset of Fig.…”
Section: Scaling Behaviormentioning
confidence: 93%
See 1 more Smart Citation
“…24 Hydrodynamic interactions are ignored in DMD and the dynamics is ballistic between collisions. Recent simulations 25 have shown, however, that the long time behavior is not affected by the short time dynamics. We use DMD because it is more efficient than…”
mentioning
confidence: 99%
“…(1) with an event-driven algorithm to detect the collisions between rod and obstacles [21][22][23]. The MSDs in fig.…”
mentioning
confidence: 99%